Conscious will and responsibility a tribute to Benjamin Libet - Libet, Benjamin, 1916-2007.; Sinnott-Armstrong, Walter, 1955-; Nadel, Lynn. (New York ; Oxford : Oxford University Press, 2010)
We all seem to think that we do the acts we do because we consciously choose to do them. This commonsense view is thrown into dispute by Benjamin Libet's experiments, which suggest that conscious will occurs not before but after the start of brain activity that produces physical action. This book explores this theory and more.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Will; Responsibility; Consciousness